2022
DOI: 10.3389/fvets.2022.852085
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Zinc Nanoparticles for the Intestinal Microbiome of Weaned Piglets

Abstract: The scientific community is closely monitoring the replacement of antibiotics with doses of ZnO in weaned piglets. Since 2022, the use of zinc in medical doses has been banned in the European Union. Therefore, pig farmers are looking for other solutions. Some studies have suggested that zinc nanoparticles might replace ZnO for the prevention of diarrhea in weaning piglets. Like ZnO, zinc nanoparticles are effective against pathogenic microorganisms, e.g., Enterobacteriaceae family in vitro and in vivo. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 162 publications
1
1
0
Order By: Relevance
“…The lightest antibacterial effect has been observed in the case of MRSA where the 2.5 mM concentration of ZnNPs inhibited bacterial growth. Our results are in agreement with similar studies which has confirmed higher antibacterial efficiency of ZnNPs on G + bacteria (Baholet et al, 2022). Malagurski et al (2017) observed antimicrobial effect of 50 mM Zn-phosphate nanocomposite film, using DDM (disk diffusion method).…”
Section: Discussionsupporting
confidence: 93%
“…The lightest antibacterial effect has been observed in the case of MRSA where the 2.5 mM concentration of ZnNPs inhibited bacterial growth. Our results are in agreement with similar studies which has confirmed higher antibacterial efficiency of ZnNPs on G + bacteria (Baholet et al, 2022). Malagurski et al (2017) observed antimicrobial effect of 50 mM Zn-phosphate nanocomposite film, using DDM (disk diffusion method).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, sufficient intake of Zn is crucial for minimizing susceptibility to bacterial infections and preserving the integrity of intestinal TJ proteins. Moreover, Zn exhibits diverse antioxidant effects, including serving as a cofactor for Cu/Zn superoxide dismutase to facilitate the conversion of superoxide radicals into less harmful H 2 O 2 , and suppressing NADPH oxidase to attenuate the production of ROS ( Baholet et al., 2022 ). Moreover, Zn serves as a cofactor for the Zim17 protein within the mitochondria, which in turn interacts with Ssc1 to facilitate both protein importation and protein folding processes within the matrix ( Pierrel et al., 2007 ).…”
Section: Antioxidant Nutrient-targeted Mitochondrial Approachesmentioning
confidence: 99%